Assessment of knowledge, attitude and practice towards infection control among dental undergraduate students-A cross-sectional survey - Charu Girotra; Siddharth Acharya; Omkar Shetty; Siddhi Savla; Mahinoor Punjani; Tanmik Shah (Wolters Kluwer Medknow Publications, 2021)
Introduction: Health-care personnel are always susceptible to infectious diseases if inadequate infection control measures are undertaken. In a dental setup, transmission occurs through air, blood, saliva droplets, or improper sterilization of instruments. Despite various standardized protocols in infection control, dental undergraduate students fail to obey the same. Aims: We aimed to assess the knowledge, attitude, and practice regarding infection control among dental undergraduate students of Mumbai. Methods: A cross-sectional questionnaire-based study comprising a 13-point close-ended, self-administered questionnaire was prepared and distributed among interns, final-year dental students, and 3rd-year dental students across six dental colleges. The questions were divided into three categories: knowledge, attitude, and practice. The responses were used for data collection and accordingly results were made. The analysis was done using IBM SPSS Statistics version 22. The statistical significance was considered at P ≤ 0.05. Results: A total of 851 undergraduate students were assessed for knowledge, attitude, and practice toward infection control. Only 40% of the interns, 40% of the final-year students, and 42% of the 3rd-year students had precise knowledge about infection control measures. Twenty-four percent of the interns, 27% of the final-year students, and 25% of the 3rd-year students showed accurate attitude for infection control. Finally, 41% of the interns, 44% of the final-year students, and 39% of the 3rd-year students inculcated right practice in controlling infection. Conclusion: Infection control is essential to reduce the risk of occupational infection to the practitioner and the auxiliary staff. Dental schools should give more emphasis on infection control protocols.